2014
DOI: 10.1212/wnl.0000000000000584
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster as a risk factor for stroke and TIA

Abstract: Objectives: Stroke and TIA are recognized complications of acute herpes zoster (HZ). Herein, we evaluate HZ as a risk factor for cerebrovascular disease (stroke and TIA) and myocardial infarction (MI) in a UK population cohort.Methods: A retrospective cohort of 106,601 HZ cases and 213,202 controls, matched for age, sex, and general practice, was identified from the THIN (The Health Improvement Network) general practice database. Cox proportional hazard models were used to examine the risks of stroke, TIA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
89
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 31 publications
(49 reference statements)
8
89
0
2
Order By: Relevance
“…In the UK, 45 % of HZ cases occurred before the age of 60 and 65 % in those under 70 [13]. Moreover, as the risk of developing HZ vasculopathy was proven to be major for subjects under 40 of age [28], the role of HZ vaccine in younger individuals could be promoted, as well as universal childhood varicella vaccination [37]. …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the UK, 45 % of HZ cases occurred before the age of 60 and 65 % in those under 70 [13]. Moreover, as the risk of developing HZ vasculopathy was proven to be major for subjects under 40 of age [28], the role of HZ vaccine in younger individuals could be promoted, as well as universal childhood varicella vaccination [37]. …”
mentioning
confidence: 99%
“…A retrospective study of 106,601 HZ cases and 213,202 age-and gender-matched controls demonstrated that HZ is an independent risk factor for vascular diseases in the UK population [28] Nagel et al [30] ''VZV vasculopathy'' could lead to transient ischemic attacks and ischemic and haemorrhagic stroke, but also temporal artery infection mimicking giant cell arteritis, extra cranial vasculopathy, aneurysm with and without subarachnoid haemorrhage, as well as spinal cord infarction and peripheral thrombotic disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notable exceptions include the following characteristics: atypical rashes, such as disseminated zoster or a minimal or absent dermatomal rash; zosteriform herpes simplex; modified (breakthrough) varicella in vaccinated individuals; and rashes caused by enteroviruses, poxviruses, rickettsia, drug reactions or contact dermatitis; and VZV infection in the absence of a rash. The latter includes, for example, zoster without rash (known as zoster sine herpete, sometimes with or without facial palsy 90 ), meningitis 1,91,92 , stroke 81,[93][94][95][96][97] , myelitis 98 and enteric (gastrointestinal) infections 45,[99][100][101][102] . In these settings, rapid diagnosis is necessary to plan appropriate therapy and public health measures.…”
Section: Diagnosis Screening and Prevention Diagnosismentioning
confidence: 99%
“…There is strong evidence that VZV infection is a risk factor for strokes [2][3][4][5][6][7][8][9]. VZV vasculopathy is seen in both immunocompetent and immunocompromised persons and can follow either varicella or zoster infection, as a result of which, populations at the extremes of age are more commonly affected.…”
Section: Introductionmentioning
confidence: 99%